Comparing users' typing performance in touch screen device (smartphone) based on QWERTY keyboard layout and screen size - Natasha Julia, anak Nyandang (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The utilization of the touch screen technology especially in smartphones are ubiquitous and have attracted many attention in today’s era. Regardless of the worldwide usage of the touch screen device (smartphone), the text entry in the device must meet the users’ expected performance despite of the different QWERTY keyboard layouts and also the screen sizes of device. Therefore, this study intended to compare users’ typing performance in touch screen device based on QWERTY keyboard layout and also screen size. The study were participated by 60 participants of the end users of touch screen device (smartphone) in Universiti Malaysia Sarawak for the typing task experiment. The results indicates that the soft QWERTY keyboard gives a higher typing speed than the gesture based QWERTY keyboard while the gesture based QWERTY keyboard gives a higher typing accuracy than the soft QWERTY keyboard. Meanwhile, or the screen size, the large screen size of the touch screen device (smartphone) gives a higher typing speed and also typing accuracy than the small and medium screen sizes. The discussion of the findings were discussed regarding the factor that contribute in the differences between users’ typing performance